STUDI EFEKTIVITAS REDUKSI KADAR FORMALIN PADA TAHU DENGAN PERENDAMAN AIR KUNYIT, AIR CUKA DAN AIR GARAM DALAM UPAYA PENYEDIAAN PANGAN AMAN - Kadek Duwi Cahyadi; Agustina Nila Yuliawati; Gusti Ayu Dewi Lestari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Tofu is one type of food made from soybeans which is widely consumed and even favored by the people of Indonesia. Based on research conducted in Manado City Health Market in 2017, 92.86% of white tofu sold in the market positively contains formalin. The high content of formalin will poison the body, cause stomach irritation, allergies, are carcinogenic (causing cancer) and are mutagenic (causing changes in cell function). In this research, a simple way to reduce formalin levels in tofu will be developed, namely immersion with turmeric water, vinegar, and salt water in formalin tofu samples (simulated samples). Optimization will be carried out on the soaking time to get the most optimal conditions to reduce the levels of formalin in tofu. The simulation sample was treated with turmeric water, vinegar and salt water for 15, 30, and 60 minutes and then tested with fehling and tollens reagents. Quantitative tests were also performed using UV-VIS spectrophotometry using chromatrophic acid reagents. Qualitative test results showed a decrease in formalin levels after soaking with turmeric water, vinegar and salt water for 60 minutes. Quantitative test results, immersion of turmeric water, vinegar and salt water for 60 minutes showed a decrease in formalin concentrations by 22.56%, 25.54% and 55.33%.